PERANAN KELOMPOK PETERNAK SAPI POTONG DENGAN PENDEKATAN SISTEM INTEGRASI PADI TERNAK (SIPT) DI NUSA TENGGARA BARAT, JAWA TIMUR, DAN JAWA BARAT - CHAIRUL MUSLIM (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
Cattle development program, such as SIPT activity, has been implemented since 2002 in 11province. In 2003, as its realization, cattle population has reached 2000 heads. This SIPTactivity is an effort to increase cattle production, as well as food production through cattleraising activities in irrigated food crop land agro ecosystem zone. The base of the programis food crop and cattle production activities with Zero Waste Base. The objective of thisresearch is to study how far the role of cattle raiser groups in implementing SIPT programis and its impact on SIPT non participant cattle raisers in West Nusa Tenggara, East Java,and West Java. The results of this study show that the role of cattle raiser groups inimplementing SIPT activities varies with the development condition in each region. Ingeneral, the cattle raiser groups have implemented and have taken the benefit of the goalsand basic concept of SIPT. Nevertheless, there are still some constrains and failures, suchas not maximally use of hay as cattle feed and not optimally use of collective cattle cage. Inthe future, government, especially local government, should be more serious in creatingconducive environment, such as good investment service and high attention to livestockdevelopment, especially cattle development.